Volume Tables for Eucalyptus camaldulensis Plantations - Jain, R. C.; Singh, Jai; Singh, Gurdev; Rawat, J. K. (Indian Forester, 1993)
In this article tables are based on tbe data collected from Eucalyptus camaldulersis plantations of New Forest. Debradun on 40 trees. Different models were tried. The equation, having the best fit for volume calculations has been used.